THE EFFECT OF CONTEMPORARY SCIENCE PHILOSOPHY ON ARCHITECTURE (Journal of Engineering, 2006)
The research tries to investigate the effects of Contemporary Science Philosophy on Architecture. The research depends on contemporary Science Philosophy of K.Popper and T.Kuhn. The procedures of the research contain the construction of comprehensive theoretical framework that includes the influence of contemporary of Philosophy of Science on Architecture in the following level which contains the general thought position, which includes (The position of Psychological Theory, knowledge Theory, the society, the history and the position of Architecture views). The conclusions of the research focus on the theoretical framework that depends on the previous views of K.Popper and T.Kuhn which reflected on Architectural views.